Animação cultural no rodeio - Moraes, Jean Cléverson (2015)
The means of this study was to describe the cultural animation on rodeo parties by social representations and actions from the professional staff. The empirical work had observation in Colorado city (South Brazil) and interviews with 12 cultural animators. The parties of rodeo became leisure and it developed in four places: 1) outside activities; 2) the great party; 3) the sports challenge; 4) music festival. There are workers to do cultural animation in rodeo parties. The bull riding is the most opportunity to this workers do cultural animation, but it gives danger to life of the clows and speakers. About this risk, the acrobatic performances had a decreasing on rodeo parties. The approach from cultural animation on rodeo is the massive entertainment. After this configuration in cultural animation on rodeo, the technology and risk management have been the resource to do cultural animation on rodeo. The speaker is the greater cultural animator in the rodeo and he does mediation between sport and public. Usually the cultural animators have to do some functions to focusing the spectator attention on rodeo: information, motivation, seduction, and entertainment. Therefore, the animation on rodeo is a special kind of cultural animation and the communication with the public and there are heritage from the rural culture together news technologies from the modern entertainment.